Narrar o passado: as matrizes do conto popular na literatura infantil em De Morte de Angela Lago - Montoro, Silvia Luciana (2009)
This research purposes to study the matrices of the popular story in children literature, showing how the narrative of Angela Lago is based on a multiple reading of the verbal and visual expression. The analysis corpus was the book De Morte. By the perspective of the theoretical approach of scholars as Teresa Colomer, Sonia Salomão Khède, Regina Zilberman, Marisa Lajolo, Alceu Maynard Araújo, we was considered the analysis of children literature and popular tradition, directed toward in order to examinate the characteristics that constituting the plan of expression of this work. The research still consists in the proposal to explore Angela Lago is fiction about the wonderful story and the popular story, analysing the typical characters of the Christian folklore, which actions follow the line of the wonderful tall according to Vladimir Propp. As a result we focused how the matrices of the popular story influence the contemporary children literature, specially of Angela Lago s fiction, demonstrating the importance of folklore in literature. The characters of the popular story, inscribed in a wonderful story, construct a new literary totality by the articulation of these two systems, the popular and the erudite. In this way the analysis would explore two strategies that are linked in the story: in the first one, verbal and visual represent the multiplicity of reading and, in the other one, the analysis of the characters by the functions according the morphologycal of study Propp. For these reason the graphical project of Angela Lago s work was examined within the intention of the popular story. Finally the research considered how the matrices of the popular story are presented in Brazilian children literature, particularies in De Morte, emphasizing how evil characts and vicious attitudes can be presented to children, without influencing negatively his cultural context